Hubungan Pola Makan Dan Status Gizi Terhadap Kejadian Hipertensi Pada Lansia Di Puskesmas Sultan Daulat Kota Subulussalam - Tuty Hertati Purba; Mariyanaq Mariyanaq; Athira Demitri Athira Demitri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Hypertension is a chronic disorder in which blood pressure in the blood vessels rises. Hypertension is characterized as having a systolic pressure of more than 140 mmHg and a diastolic pressure greater than 90 mmHg. The study aimed to assess the impact of food and nutritional status on the prevalence of hypertension in the elderly at Sultan Daulat Health Centre in Subulussalam City. The study was an analytic observational design with a case control. All older adults at the Sultan Daulat Health Centre in Subulussalam City who were hypertensive or not were included in the research. The case sample consisted of 22 hypertensive respondents, while the control sample consisted of 22 non-hypertensive respondents. The chi-square statistical test was used to assess data bivariately The results showed that there was a relationship between diet with a p-value of 0.004 <05 and OR 7.600 (95% CI) 1.732 – 33.347, fat intake with a p-value of 0.001 <05 and OR 13.571 (95% CI) 2.991 – 61.586, sodium intake with a p-value 0.000<05 and OR 12.000 (95% CI) 2.862 – 50.306 and nutritional status with a p-value of 0.002<05 and OR 9.643 (95% CI) 2.362 – 39.365 with the incidence of hypertension in the elderly at the Sultan Daulat Health Centre, Subulussalam. This study's recommendations were intended to regulate a balanced diet, minimize consumption of foods high in fat and sodium, and eat foods high in fiber to control excess body weight.